Experimental investigation of void distribution in suppression pool over the duration of a loss of coolant accident using steam–water two-phase mixture. (January 2015) - Rassame, Somboon; Griffiths, Matthew; Yang, Jun; Ju, Peng; Sharma, Subash; Hibiki, Takashi; Ishii, Mamoru
Highlights: Experiments were conducted to study void fraction distribution in SP during blowdown. 3 Experimental phases, namely, an initial and a quasi-steady phase, chugging were observed. The maximum void penetration depth was experienced during the initial phase. The quasi-steady phase provided less void penetration depth with oscillations. The chugging phase was experienced at the end of experimental phase. Abstract: Studies are underway to determine if a large amount gas discharged through the downcomer pipes in the pressure suppression chamber during the blowdown of Loss of Coolant Accident (LOCA) can potentially be entrained into the Emergency Core Cooling System (ECCS) suction piping of BWR. This may result in degraded ECCS pumps performance which could affect the ability to maintain or recover the water inventory level in the Reactor Pressure Vessel (RPV) during a LOCA. Therefore, it is very important to understand the void behavior in the pressure suppression chamber during the blowdown period of a LOCA. To address this issue, a set of experiments is conducted using the Purdue University Multi-Dimensional Integral Test Assembly for ESBWR applications (PUMA-E) facility. The geometry of the test apparatus is determined based on the basic geometrical scaling analysis from a prototypical BWR containment (MARK I) with a consideration of downcomer size, downcomer water submergence depth and Suppression Pool (SP) water level. Several instruments are installed in the test facility to measure the required experimental data such as the steam mass flow rate, void fraction, pressure and temperature. In the experiments, sequential flows of air, steam–air mixture and pure steam-each with the various flow rate conditions are injected from the Drywell (DW) through a downcomer pipe in the SP. Eight tests with two different downcomer sizes, various initial gas volumetric fluxes at the downcomer, and two different initial non-condensable gas concentration conditions in the DW are conducted. Three distinct phases, namely, an initial phase, a quasi-steady, and a chugging phase are observed. The maximum void penetration depth is observed in the initial phase. A reduction in the void penetration depth is observed in the quasi-steady phase. As a result of low non-condensable gas concentration, chugging is observed at the tail end of the experiment. Chugging provides renewed void penetrations comparable to those in the initial phase. It is determined that the void distribution and area of void penetration in the SP is governed by the gas volumetric flux at the downcomer and the non-condensable gas concentration in the downcomer.